Impact of new definitions of preeclampsia at term on identification of adverse maternal and perinatal outcomes - Lai, Jonathan; Syngelaki, Argyro; Nicolaides, Kypros H.; von Dadelszen, Peter; Magee, Laura A. (American journal of obstetrics and gynecology, 2021)
Any definition of preeclampsia should identify women and babies at greatest risk of adverse outcomes. This study aimed to investigate the ability of the American College of Obstetricians and Gynecologists and International Society for the Study of Hypertension in Pregnancy definitions of preeclampsia at term gestational age (≥37 0/7 weeks) to identify adverse maternal and perinatal outcomes. In this prospective cohort study at 2 maternity hospitals in England, women attending a routine hospital visit at 35 0/7 to 36 6/7 weeks’ gestation underwent assessment that included history; ultrasonographic estimated fetal weight; Doppler measurements of the pulsatility index in the uterine, umbilical, and fetal middle cerebral arteries; and serum placental growth factor–to–soluble fms-like tyrosine kinase-1 ratio. Obstetrical records were examined for all women with chronic hypertension and those who developed new-onset hypertension, with preeclampsia (de novo or superimposed on chronic hypertension) defined in 5 ways: traditional, based on new-onset proteinuria; American College of Obstetricians and Gynecologists 2013 definition; International Society for the Study of Hypertension in Pregnancy maternal factors definition; International Society for the Study of Hypertension in Pregnancy maternal factors plus fetal death or fetal growth restriction definition, defined according to the 35 0/7 to 36 6/7 weeks’ gestation scan as either estimated fetal weight <3rd percentile or estimated fetal weight at the 3rd to 10th percentile with any of uterine artery pulsatility index >95th percentile, umbilical artery pulsatility index >95th percentile, or middle cerebral artery pulsatility index <5th percentile; and International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance definition, defined as placental growth factor <5th percentile or soluble fms-like tyrosine kinase-1–to–serum placental growth factor >95th percentile. Detection rates for outcomes of interest (ie, severe maternal hypertension, major maternal morbidity, perinatal mortality or major neonatal morbidity, neonatal unit admission ≥48 hours, and birthweight <10th percentile) were compared using the chi-square test, and P<.05 was considered significant. Among 15,248 singleton pregnancies, the identification of women with preeclampsia varied by definition: traditional, 15 of 281 (1.8%; 248); American College of Obstetricians and Gynecologists, 15 of 326 (2.1%; 248); International Society for the Study of Hypertension in Pregnancy maternal factors, 15 of 400 (2.6%; 248); International Society for the Study of Hypertension in Pregnancy maternal-fetal factors, 15 of 434 (2.8%; 248); and International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance, 15 of 500 (3.3%; 248). Compared with the traditional definition of preeclampsia, the International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance best identified the adverse outcomes: severe hypertension (40.6% [traditional] vs 66.9% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance, P<.0001], 59.2% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors, P=.004], 56.2% [International Society for the Study of Hypertension in Pregnancy maternal factors, P=.013], 46.1% [American College of Obstetricians and Gynecologists, P=.449]); P<.0001); composite maternal severe adverse event (72.2% [traditional] vs 100% for all others; P=.046); composite of perinatal mortality and morbidity (46.9% [traditional] vs 71.1% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance, P=.002], 62.2% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors, P=.06], 59.8% [International Society for the Study of Hypertension in Pregnancy maternal factors, P=.117], 49.4% [American College of Obstetricians and Gynecologists, P=.875]); neonatal unit admission for ≥48 hours (51.4% [traditional] vs 73.4% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance, P=.001], 64.5% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors, P=.070], 60.7% [International Society for the Study of Hypertension in Pregnancy maternal factors, P=.213], 53.3% [American College of Obstetricians and Gynecologists, P=.890]); birthweight <10th percentile (40.5% [traditional] vs 78.7% [International Society for the Study of Hypertension in Pregnancy maternal-fetal factors plus angiogenic imbalance, P<.0001], 70.1% [International Society for the Study of Hypertension in Pregnancy maternal-fetal, P<.0001], 51.3% [International Society for the Study of Hypertension in Pregnancy maternal factors, P=.064], 46.3% [American College of Obstetricians and Gynecologists, P=.349]). Our findings present an evidence base for the broad definition of preeclampsia. Our data suggest that compared with a traditional definition, a broad definition of preeclampsia can better identify women and babies at risk of adverse outcomes. Compared with the American College of Obstetricians and Gynecologists definition, the more inclusive International Society for the Study of Hypertension in Pregnancy definition of maternal end-organ dysfunction seems to be more sensitive. The addition of uteroplacental dysfunction to the broad definition optimizes the identification of women and babies at risk, particularly when angiogenic factors are included.